2014
DOI: 10.1007/s13311-014-0283-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cortical Stimulation in Neuropathic Pain, Tinnitus, Depression, and Movement Disorders

Abstract: Medical treatment must strike a balance between benefit and risk. As the field of neuromodulation develops, decreased invasiveness, in combination with maintenance of efficacy, has become a goal. We provide a review of the history of cortical stimulation from its origins to the current state. The first part discusses neuropathic pain and the nonpharmacological treatment options used. The second part covers transitions to tinnitus, believed by many to be another deafferentation disorder, its classification, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…It has been suggested that the direct stimulation of the PFC may serve to modulate temporo-parietal attentional networks involved in the automatic processing of salient stimuli [30], playing a critical role in mood regulation [55]. In this sense, cortical stimulation for treatment-resistant depression constitutes a brain stimulation approach that has shown promise [5658]. Here, we show that mPFC-DBS affected metabolic activity in the striatum, temporal and piriform cortices, the amygdala, cerebellum, brainstem and periaqueductal gray matter.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the direct stimulation of the PFC may serve to modulate temporo-parietal attentional networks involved in the automatic processing of salient stimuli [30], playing a critical role in mood regulation [55]. In this sense, cortical stimulation for treatment-resistant depression constitutes a brain stimulation approach that has shown promise [5658]. Here, we show that mPFC-DBS affected metabolic activity in the striatum, temporal and piriform cortices, the amygdala, cerebellum, brainstem and periaqueductal gray matter.…”
Section: Discussionmentioning
confidence: 99%
“…From 1938 on, ECT was applied broadly in people diagnosed with severe mania and depression (Bajbouj and Heuser 2009; Bethune 2007; Lewis and others 2016; Panov and Kopell 2014). A rationale was that there was no hope to relieve people from suicidal ideation and severe depression until its appearance (Bethune 2007).…”
Section: Ect In International Medicine and People Suffering From Mental Illnessesmentioning
confidence: 99%
“…In 1940, Rivista Sperimentale di Freniatria, published in a 600 pages report, an extensive presentation of ECT composed by Cerletti and his followers (Mora 1963). The main points of this report were the protocol for the method of application of ECT (Zivotofsky and Strous 2012), its mechanism of action, the necessity for further studies on ECT (Mora 1963), the low cost of the therapy (Mora 1963), and the article included a discussion of the beneficial—especially in patients suffering from intractable depression and schizophrenia (Grözinger and others 2015; Mora 1963; Panov and Kopell 2014; Rasmussen 2003)—and nonbeneficial parts of ECT (Mora 1963).…”
Section: Ect In International Medicine and People Suffering From Mental Illnessesmentioning
confidence: 99%
“…With advances in stimulation, the increasing sophistication of these procedures will continue. We will see, for example, closed loops stimulation systems, as outlined by Sun and Morell [9], and an increasing number of electrode designs and feedback mechanisms, including the examination of implanted cortical electrodes to treat a variety of disorders (Panov and Kopell [10]), and to enhance plasticity and recovery after stroke (Plow and Machado [11]). …”
Section: Implanted Devices Can Be Targeted Quite Precisely To Affectmentioning
confidence: 99%